2007
DOI: 10.1093/ajcn/86.5.1595
|View full text |Cite
|
Sign up to set email alerts
|

Novel calcium-gelled, alginate-pectin beverage reduced energy intake in nondieting overweight and obese women: interactions with dietary restraint status

Abstract: Background: Foods containing strong-gelling fibers may provide a safe and efficacious strategy for reducing food intake by stimulating endogenous satiety signaling. Objective: A novel, 2-part beverage, consisting of alginate-pectin and calcium components, that forms a stable, fibrous gel in the stomach was tested to determine its effects on subjective satiety and food intake in overweight and obese women. Design: The investigation was a within-subjects, double-blind, placebo-controlled study. Subjects (n ҃ 29)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 50 publications
2
45
2
2
Order By: Relevance
“…Satiety was also improved in a study by Peters et al (2006) in which both weak-and strong-gelling alginate ingestion was compared to low-and high-viscosity guar gum and a control; however, food intake was not measured. Contrary to the food intake findings presented above, Pelkman et al (2007) found that a calcium gelled alginate-pectin beverage (of differing strengths) ingested twice daily significantly reduced energy intake in overweight and obese women with low rigid restraint scores.…”
Section: Introductioncontrasting
confidence: 99%
“…Satiety was also improved in a study by Peters et al (2006) in which both weak-and strong-gelling alginate ingestion was compared to low-and high-viscosity guar gum and a control; however, food intake was not measured. Contrary to the food intake findings presented above, Pelkman et al (2007) found that a calcium gelled alginate-pectin beverage (of differing strengths) ingested twice daily significantly reduced energy intake in overweight and obese women with low rigid restraint scores.…”
Section: Introductioncontrasting
confidence: 99%
“…This product was developed to examine the effect of whey protein on satiety and for another study not described in this manuscript, to examine the effects on the musculoskeletal system and body composition. A protein-free placebo drink was also developed using alginate, known for its viscosity and satiety effect (Pelkman et al 2007, Paxman et al 2008.…”
Section: Procedures and Experimental Designmentioning
confidence: 99%
“…Willis (2009) found the inclusion of resistant starch and corn bran in muffins enhanced short-term satiety when compared with those made with polydextrose. Pelkman et al (2007) and Paxman et al (2008) found consumption of sodium alginate or alginate-pectin plus calcium based food resulted in a reduction of subsequent energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to energy intake (Tredger et al, 1991;Haskell et al, 1992;Pasman et al, 1997b;Panlasigui et al, 2003;Marett & Slavin, 2004;Schwab et al, 2006;Garcia et al, 2007;Mattes, 2007;Pelkman et al, 2007;Wood et al, 2007;Paxman et al, 2008), seven of which were included in a meta-analysis (Tredger et al, 1991;Pasman et al, 1997b;Schwab et al, 2006;Garcia et al, 2007;Pelkman et al, 2007;Wood et al, 2007;Paxman et al, 2008). Four trials could not be included in metaanalysis but demonstrated no statistically significant effect of soluble fibre isolates on energy intake (Haskell et al, 1992;Panlasigui et al, 2003;Marett & Slavin, 2004;Mattes, 2007).…”
Section: Energy Intakementioning
confidence: 99%
“…Five randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to eating motivation (Pasman et al, 1997b;Heini et al, 1998;Schwab et al, 2006;Mattes, 2007;Pelkman et al, 2007). (Cardio-metabolic review, Energy intake and eating motivation chapter p 150-152).…”
Section: Eating Motivationmentioning
confidence: 99%